"Contribution à l’étude de la qualité des eaux d’Oued Ittel à la commune de Still « Wilaya d’El M’Ghair » " - الاخضر, صادقي; محمد المحسن, كساب (University of El-Oued, 2022)
"In this research we covered the chemical-physical analysis of farming water in segment of valley Ittel part of commune Still areas of the country El M’Ghair. The tests done on these water samples showed that they differ although they come from the same sources (groundwater). By comparing the obtained results with the Algerian Temporarily Standards (NPA) table and the WHO norms we concluded that the water destined for farming as Still areas of the Country El M’Ghair should be closely studied in order to know more about the its different composites and her concentrations. This will help avoid any health problems which may subject people. " "تناولنا في هذا البحث التجارب التحليلية الفيزيائية والكيميائية لمياه الطبقة السطحية الموجهة للسقي الفلاحي في جزء من وادي إيتل الذي يمر ببلدية سطيل ولاية المغير و من خلال التجارب التي قمنا بها على عينات لاحظنا أن هناك اختلاف واضح في النتائج رغم أنها من نفس المصدر (مياه الطبقة السطحية) ومع مقارنتها بجداول المعايير لمنظمة الصحة العالمية (OMS) و لمنظمة الصحة الجزائرية (NPA) خلصنا إلى أن المياه الموجهة للسقي الفلاحي يجب أن تخضع إلى دراسات تحليلية معمقة للتعرف أكثر على العناصر المكونة لها و كذا تراكيزها لتفادي الاضرار الصحية التي قد يتعرض لها الانسان. "
مذكرات ماستر تخصص ري
Keywords: Keywords: Still (El M’Ghair), Groundwater, Valley Ittel , Carte, Chemical-physical analysis; الكلمات المفتاحية: سطيل (المغير)، الطبقة السطحية، وادي إيتل، خارطة، تحاليل فيزيائية و كيميائية.